Pengaruh Keterampilan Proses Sains terhadap Kemampuan Bernalar Kritis Anak Usia 5-6 Tahun di TK IT Insan Teladan Pekanbaru - Husni Ibadatika Arif; Zulkifli N; Daviq Chairilsyah (Departement of Mathematics Education, 2024)
Science process skills influence the critical reasoning abilities of children aged 5-6 years. This research aims to determine the influence of science process skills on the critical reasoning abilities of children aged 5-6 years at the Insan Teladan IT Kindergarten in Pekanbaru. This research is quantitative research with a correlational type of research. The population of this study was 88 children aged 5-6 years at the IT Insan Teladan Pekanbaru Kidergarten, the sample used was 88 children. This research is a quantitative correlation research with a correlation test using the Pearson Product Moment formula. The sampling technique used in this research is the saturated sampling technique. The data collection technique used is observation. In this research, the hypothesis proposed is that there is an influence of science process skills on the critical reasoning abilities of children aged 5-6 years at the Insan Teladan IT Kindergarten in Pekanbaru. The resulting determinant coefficient value is r2 = 0,735, meaning 73,5% which means that science process skills have a 73,5% influence on critical reasoning abilities. This shows that there is an influence that science process skills have on the critical reasoning abilities of children aged 5-6 years at the Pekanbaru Insan Teladan IT Kindergarten.